Uncovering the role of microRNAs in esophageal cancer: from pathogenesis to clinical applications - He, Zhenglin; Ji, Yishuo; Yuan, Yutong; Liang, Tianfang; Liu, Chenglin; Jiao, Yiping; Chen, Yimeng; Yang, Yiming; Han, Liang; Hu, Yue; Cong, Xianling (Frontiers in Pharmacology, 2025)
Esophageal cancer (EC) presents substantial therapeutic challenges due to its high mortality rate and the tendency for diagnosis at advanced stages. Acknowledging the constraints of the existing current treatment paradigm, there is a pressing need for the development of innovative, targeted therapeutic strategies to surpass the current stagnation in survival rate improvements. Recently, microRNAs (miRNAs) have attracted significant attention for their capacity to regulate gene expression at the post-transcriptional level, thereby influencing various cellular processes. In this review, we provide a comprehensive analysis of the role of miRNAs in EC, emphasizing their mechanisms in tumorigenesis, their potential as diagnostic and prognostic biomarkers, and their influence on resistance to therapy. We elucidate how miRNAs modulate oncogenic pathways and tumor suppressor genes, influencing EC cell behavior and treatment outcomes. By integrating insights from genetic sequencing and molecular biology, we identify key miRNAs that promote or inhibit EC progression and treatment resistance. This review highlights critical need for an enhanced understanding of miRNAs in EC, advocating for their integration into therapeutic strategies.